Atypical Eating Behaviors Identified in Children with Fetal Alcohol Spectrum Disorders, Aged 3 to 5 Years, Using the Children’s Eating Behavior Questionnaire in a Caregiver-Reported Online Survey - Evans, Shirley F.; Payton, Mark; Kennedy, Tay (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Background: Children with fetal alcohol spectrum disorders (FASDs), aged 3 to 5 years, have physical, behavioral, and functional problems. Because of alcohol-related deficits, children with FASDs are at risk for malnutrition; yet, little is known about how FASD affects eating behavior and nutrition. Aim: The purpose of this study was to identify atypical eating behavior in children with FASDs, aged 3 to 5 years, and their associations with socio-demographic characteristics. Method: This descriptive cross-sectional study gathered data from a caregiver-reported online survey targeting the eating behavior of preschool-aged children with FASDs. The survey included the Children’s Eating Behavior Questionnaire (CEBQ) and a socio-demographic questionnaire. Participants/Setting: Seventy-four caregivers qualified for the study with nine having two children with FASDs. Responses to survey questions varied since caregivers had permission to omit any question. Results: Significant differences were found between the preschool-aged children with FASDs and Wardle’s published normative sample by gender and age. Compared to reported norms, study children scored higher in Desire to Drink, Food Responsiveness, Emotional Overeating, and Food Fussiness, and lower in Enjoyment of Food. Regarding socio-demographic characteristics, there was greater Enjoyment of Food with larger families and Food Avoidance with college-educated caregivers. Conclusion: Children with FASDs, aged 3 to 5 years, have atypical eating behaviors characteristic of maladaptive appetites, overeating under stress, selective eating, slowness in eating, and an excessive need for drinks, in comparison with a published normative sample.